Pengaruh Konflik dan Stres Kerja Terhadap Kinerja Karyawan Pada Dinas Lingkungan Hidup Kota Probolinggo - Eka Hanis Nurwanto; Supriyono Supriyono (Ecobuss, 2017)
This research was conducted in DLH Kota Probolinggo with the aim to know whether conflict (X1) and work stress (X2) have significant partially and simultaneously effect on employee performance at DLH Kota Probolinggo. Research type used is quantitative, with research variables used to consist of three kinds of variables that are independent variable (conflict and work stress) and the dependent variable (performance). Population in this research is 20% of a total employee at DLH Town of Probolinggo that is equal to 90 responders. Data analysis method used is quantitative analysis. The results showed that the results of the analysis F test known together Conflict and Work Stress significantly influence employee performance in DLH Probolinggo city. Based on the results of the F statistic test shows the value of 64,079 with a significance of 0.000. then Ho is rejected and Ha accepted. Partially work conflict is significant and significant to employee performance at Probolinggo Town DLH. Based on the results of t-test partial coefficient value of 5.411 with a significance of 0.000 then Ho is rejected and Ha accepted. And partially work stress also have an effect and significant to employees performance at DLH Town of Probolinggo. Based on the results of partial t-test shows the coefficient of 3.936 with the significance of 0.000 then Ho is rejected and Ha accepted. Keywords: Employee Performance, Conflict, Job Stress